The Role of Abhyantara Snehapana in Ayurveda Management (AYUSHDHARA, 2024)
Shodhananga Snehapana is a crucial preparatory therapy in Ayurveda, performed before the Shodhana procedures (Vamana and Virechana) in the Panchakarma regimen. It involves the internal administration of medicated oils or fats (Sneha), designed to promote the Snigdha (unctuous) quality in the body. Snehapana facilitates the softening and loosening of accumulated morbid Doshas (toxins) in the body, making them easier to expel during subsequent detoxification therapies. It enhances the circulation of Rasa Dhatu (plasma) and promotes moisture (Klinnata) in the tissues, which helps in alleviating dryness and balancing the Vata dosha. This procedure also strengthens the body and improves the digestive fire (Agni), ensuring better absorption and assimilation of nutrients. Shodhananga Snehapana, as a preparatory procedure, optimizes the body’s condition for the effective purification of excess Doshas, leading to a state of balance and improved health.